Associations between multiple indicators of discrimination and allostatic load among middle-aged adults. (April 2022) - Lawrence, Jourdyn A.; Kawachi, Ichiro; White, Kellee; Bassett, Mary T.; Williams, David R.
Abstract: The objective of this paper is to examine associations between multiple measures of discrimination (i.e., everyday, lifetime, and appraised burden) and components of allostatic load (AL). We drew on pooled cross-sectional data from the Biomarker Project of the Midlife in the United States study (n = 2118). Ages ranged from 25 to 84 years and included mostly Black (n = 389) and white (n = 1598) adults. Quasi-Poisson models were fit to estimate prevalence ratios for each discrimination measure and high-risk quartiles across seven physiological systems (i.e., sympathetic and parasympathetic nervous system; HPA axis; inflammation; cardiovascular; metabolic glucose; and metabolic lipids) and overall AL scores. In fully adjusted models, everyday discrimination was associated with elevated lipids (aPR: 1.07; 95% CI 1.01, 1.13). Lifetime experiences of discrimination were associated with lower sympathetic nervous system (aPR: 0.82; 95% CI: 0.69, 0.98) and greater cardiovascular risk scores (aPR: 1.17; 95% CI: 1.02, 1.34) among those reporting three or more experiences, as well as increased inflammation (aPR: 1.13; 95% CI: 1.02, 1.25; aPR: 1.28; 95% CI: 1.14, 1.43), metabolic glucose (aPR: 1.35; 95% CI: 1.19, 1.54; aPR: 1.45; 95% CI: 1.24, 1.68), and metabolic lipids (aPR: 1.13; 95% CI: 1.03, 1.24; aPR: 1.28; 95% CI: 1.15, 1.43) scores for those reporting one to two and three or more experiences. Appraised burden yielded nuanced associations with metabolic glucose and parasympathetic nervous system scores. Everyday and lifetime measures were also associated with higher overall AL, though burden of discrimination was only associated with AL among those reporting "a little" burden. While AL summary scores provide insight into the cumulative impacts of discrimination on health, there appear to be distinct physiologic pathways through which varying forms of discrimination contribute to AL and, ultimately, to poorer health. These unique pathways may be useful in identifying potential points of intervention to mitigate the impacts of discrimination on health inequities. Highlights: Patterns between measures of discrimination and allostatic load vary. Associations between discrimination measures and individual biomarkers also vary. Distinct pathways between forms of discrimination and allostatic load may exist. These variations may be useful in mitigating the health impacts of discrimination.